2010
DOI: 10.1126/scitranslmed.3001513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correction of PSA Values Using Sequence Variants Associated with PSA Levels

Abstract: Measuring serum levels of the prostate specific antigen (PSA) is the most common screening method for prostate cancer. However, PSA levels are affected by a number of factors apart from neoplasia. Notably, around 40% of the variability of PSA levels in the general population is accounted for by inherited factors, suggesting that it may be possible to improve both sensitivity and specificity by adjusting test results for genetic effects. In order to search for sequence variants that associate with PSA levels, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
172
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 26 publications
8
172
1
2
Order By: Relevance
“…Furthermore, two articles lacking usable data were not used in our meta-analysis. One article studying 5009 cases and 41334 controls showed that the TERT rs2736098 polymorphism is associated with prostate cancer (Gudmundsson et al, 2010), The other article studied 11290 cancer patients and 31162 controls and showed that TERT rs2736098 A variant genotypes are associated with significant increases in risk for basal cell carcinoma, lung cancer, bladder cancer and prostate cancer but not of cervical cancer in the European population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two articles lacking usable data were not used in our meta-analysis. One article studying 5009 cases and 41334 controls showed that the TERT rs2736098 polymorphism is associated with prostate cancer (Gudmundsson et al, 2010), The other article studied 11290 cancer patients and 31162 controls and showed that TERT rs2736098 A variant genotypes are associated with significant increases in risk for basal cell carcinoma, lung cancer, bladder cancer and prostate cancer but not of cervical cancer in the European population.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the individual studies is shown in Table 1. Two studies (Rafnar et al,2009;Gudmundsson et al, 2010) were not included in our meta-analysis for reasons outlined in the Discussion section.…”
Section: Data Extractionmentioning
confidence: 99%
“…26,27 For each SNP not present on the Affymetrix 6.0 array, pairwise linkage disequilibrium (LD), as measured by r 2 , was computed using genotype data from residents of Utah with northern and western European ancestry (HapMap3 CEU population; Altshuler et al; 28 http://hapmap.ncbi.nlm.nih.gov/). For each SNP, the SNP on the Affymetrix 6.0 array with the strongest LD was selected as the tag SNP.…”
Section: Snp Selectionmentioning
confidence: 99%
“…2,[5][6][7][8][9][10][11] The genetic variability of the telomerase reverse transcriptase (TERT) and the telomerase RNA component (TERC) gene regions could play a role in MM etiology for two reasons: first the two genes are responsible for crucial cellular processes, namely telomere homeostasis, second their polymorphic variants have been found to be associated with multiple cancer types and other human phenotypes. [12][13][14][15][16][17][18][19][20][21][22][23][24] TERT and TERC constitute the telomerase complex, 25 whose correct functioning is fundamental for the accurate de novo synthesis of telomeric ends. Even moderate changes in TERT and TERC activity could profoundly affect telomere homeostasis.…”
mentioning
confidence: 99%
“…12,14,15 In addition, TERT polymorphisms are associated with other human phenotypes such as pulmonary fibrosis and PSA levels. [22][23][24]34 A very recent GWAS has reported the association of rs10936599 with increased risk of MM. 7 This polymorphism lies in 3q26.2, in a linkage disequilibrium (LD) region that includes also the TERC gene.…”
mentioning
confidence: 99%